The Philosophy and Practice of Medicine and Bioethics A Naturalistic-Humanistic Approach - Maier, Barbara; Shibles, Warren A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book explores currently unchallenged methods in medicine, such as (3z(Bevidence-based medicine(3y(B, from the perspectives of humanism and philosophy of medicine. The book discusses issues of medical treatment and moral approaches and indicates the strongest arguments. These arguments are subsequently subjected to critical analysis. The book includes new ways of thinking and explains, uses and exemplifies the (3z(Bmetaphorical method(3y(B. The book argues that decision-making in medicine is inadequate unless grounded on a philosophy of medicine. As part of its argumentation, the book explores the insights offered by practical and humanistic philosophy and by creative and critical thinkers who are working on topics relevant to medicine. From this, a new and necessary definition of philosophy of life emerges: a good lifestyle no longer simply means getting physical exercise and abstaining from cigarettes and alcohol; it also means living a holistic life including all of one$1 (Bs thinking, personality and actions.s
Rationale of the book -- About the Authors -- 1. Metaphor in Medicine. The Metaphorical Method -- 2. Definition -- 3. Decision Making: fallacies and other mistakes -- 4. Analysis of Causation in Medicine -- 5. Ethics and Non-Ethics -- 6. Medicotheology and Biotheology -- 7. Emotion in Medicine -- 8. Enlightened Versus Normative Management. Ethics Versus Morals. -- 9. Care: A Critique of the Ethics and Emotion of Care -- 10. Egoism and Altruism in Medicine -- 11. Letting Die -- 12. A Critique of Autonomy and Patient Responsibility -- 13. Philosophy and Ethics of the Body -- 14. Organ Donation: Mandatory Organ Donation Declaration -- 15. Stem Cell Research: A Question of Beliefs? -- 16. Philosophy of Prevention -- 17. Ethics Counseling: Philosophy of Medicine Counseling Instead of Medical Ethics Counseling -- 18. Medical Language: The Ordinary Language Approach -- 19. A Critique of Evidence-Based Medicine. Evidence Based Medicine and Philosophy Based Medicine -- 20. Lying in Medicine -- 21. Rhetoric of Death and Dying -- Index.
Keywords: Medicine; Medical ethics; Medicine & Public Health; Theory of Medicine/Bioethics.